ҚУЁШ ЭЛЕМЕНТИ ЁРДАМИДА ЭНЕРГИЯНИНГ БИР ТУРДАН БОШҚА ТУРЛАРГА УЗЛУКСИЗ ЎТИШИНИ НАМОЙИШ ЭТУВЧИ ЎҚУВ ЛАБОРАТОРИЯ ҚУРИЛМАСИ - Қурбонова, Ў.Ҳ.; Сатторов, А.А. (SCIENCE and SOCIETY, 2020)
In this paper, tere is used the functionality of solar cells, shows the structure and principle of operation of the developed new educational device, with the help of which explains one of the interesting phenomena as the transformation of energy from one species to another, the law of conservation of energy during this process. Moreover, it describes the methods of teaching students the structure, the principle of operation and features of solar cells. The developed educational device demonstrates to students the transition of electrons from the valence band to the conduction band as a result of the incidence of light on a solar cell created on the basis of semiconductor silicon based on p-n transition, that is the performance of the solar cell as an electric source due to the separation in the p-n region of electrons and holes arising from the internal photoelectric effect.